Are Credit Ratings Valuable Information? - Kornelius Kraft; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Credit ratings are commonly used by lenders to assess the default risk, because every credit is connected with a possible loss. If the probability of a default is above a certain threshold, a credit will not be provided. The purpose of this paper is to test whether credit ratings contribute valuable information on the creditworthiness of firms. Employing a large sample of Western German manufacturing firms, we investigate loan defaults. First, we estimate Probit models with publicly available information. Subsequently, we additionally use a credit rating and show that it contributes significantly to the regression fit. However, the publicly available information has an independent effect aside of the ratings. Simple calculations demonstrate that the interest rate has to increase significantly to compensate for a possible loss in case of default, if a firm has a weak rating.
Keywords: C25; G33; 330; Credit Rating; Insolvency; Loan Default; Discrete Regression Models; Kreditwürdigkeit; Kreditrisiko; Informationswert; Schätzung; Deutschland